Exploring the Japanese ways of life - Shunkichi, Akimoto (Tokyo News Service, 1961)
In this book, the author in his inimitable way makes the usually "difficult-to-swallow" pill called culture and even more "difficult-to-get-at" thing called ways of life, very palatable and interesting, even to casual readers. Yet the wealth and accuracy of information behind the easy appearance of the work makes it a satisfying book also to students of Japanese ways of life.